Leadership for sustainability : strategies for tackling wicked problems - Hull, Robert Bruce, 1957-; Robertson, David P.; Mortimer, Michael (Washington Island Press, 2020)
"Solving today's environmental and sustainability challenges requires more than expertise and technology. Effective solutions will require that we engage with other people, wrestle with difficult questions, and learn how to adapt and make confident decisions despite uncertainty. We need new approaches to leadership that empower professionals at all levels to tackle wicked problems and work towards sustainability. Leadership for Sustainability gives readers perspective and skills for promoting creative and collaborative solutions. Blending systems thinking approaches with leadership techniques, it offers dozens of strategies and specific practices, illustrated by inspiring case studies. Readers will come away with a holistic understanding of how to lead from where they are by applying leadership principles and practices to a wide range of wicked situations"--